Ungdomars tankar kring ägarskifte inom lantbruket - Lundin, Milan (2019)
Introduction: Many people who have a connection to agriculture will at some time be affected by a change of ownership. Roles that then become involved are the transferor, the transferee, the siblings and third parties (neighbor, consultant, employee). Everything from economy, law, production, leadership to life puzzles, emotions and values are topics that concern ownership change. Ownership is often a big event, where the future and history meets. (Bucht, R., Kindlund, P., Lindberg, J. & Odén, C., 1990) (Petersson, P.H., 1981).